Electro-thermal numerical analysis of microbolometer over various kinds of design structure under adjustable thermal conductance in the Microeletromechanical system - Yanan Xu; Mukti Rana; Kevin Díaz-Aponte (Heliyon, 2023)
The microbolometer is an important device that has a variety of civilian, industrial, and military applications, especially in remote sensing and night vision. Microbolometers are sensor elements in uncooled infrared sensors, which makes the uncooled infrared sensors have the advantage of being smaller in size, light in weight and less expensive compared with cooled infrared sensors. If the microbolometers are arranged in a two-dimensional array, a thermo-graph of the object can be determined using a microbolometer based uncooled infrared sensor. Building the electro-thermal modeling over the microbolometer pixel is essential to determine the uncooled infrared sensor's performance, optimize the sensor's design structure and monitor its condition. Due to the fact that the knowledge for the complex semiconductor-material-based microbolometers over various kinds of design structures with the adjustable thermal conductance is limited so far, this work focuses on the thermal distribution first by considering factors of the radiation absorption, thermal conductance, convection feature and joule heating on varied geometry design structures using Finite Element Analysis (FEA) methods. Then the change of thermal conductance is depicted when the simulated voltage is applied quantitatively between the microplate and electrode through the dynamic interaction of the electro force and the structure deformation via the electro particles redistribution balance by utilizing the Microeletromechanical system (MEMS). In addition, a more accurate contact voltage is derived through the numerical simulation compared with the previous theoretical value and is also verified by the experiment.